TOTAL PHENOLIC CONTENTS AND ANTIOXIDANT ACTIVITIES OF SUB-FRACTIONS FROM STEM BARKS OF Casearia grewiifolia - Nuanyai, Thanesuan; Chailap , Benjamat (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The ethyl acetate extracts of the stem bark of Casearia grewiifolia were separated by column chromatography technique. The 13 sub-fractions extracts were isolated by increasing polarity of the eluent. Based on the antioxidant activity analysis using DPPH technique, the sub-fractions 1-9 (5-30% Ethyl acetate/Hexane) displayed antioxidant values at the level of IC50 greater than 100 µg / mL and sub-fractions 10 -13 (35-50% Ethyl acetate/Hexane) showed an antioxidant at IC50 values in the range of 37.25 - 27.23 µg/mL. While, the Trolox standard substance exhibited an antioxidant level of IC50 at 5.28 ± 0.83 µg/mL. In addition, the antioxidant activity by ABTS technique, the sub-fractions 1 – 10 (5-35% Ethyl acetate/Hexane) showed the IC50 value more than 100 µg/mL, and the sub-fractions 11-13 (40-50% Ethyl acetate/Hexane) displayed the antioxidant value at IC50 in the range of 26.13 - 48.03 µg/mL, while Trolox standard substance had an antioxidant activity at IC50 value at 18.44 ± 1.06 µg/mL. Moreover, the total phenolic content of the sub-fractions 1 - 13 were in the range of 15.56 - 367.96 mgGAE/g. The sub-fraction 13 displayed the highest total phenolic content value. It was found that the total phenolic content correlated with the antioxidant activity using DPPH and ABTS assay. In conclusion, the polarity of extract was play an important role in the phenolic content and antioxidant activities.